Pediatric Trauma 2020 : Bringing the Best Care to Children. - Mark, Shelly; Dietrich, Ann. (Morrisville, NC : Relias LLC, 2019)
The latest installment in an award-winning series, Pediatric Trauma 2020: Bringing the Best Care to Children facilitates excellence by covering the latest scientific information on caring for children who present with traumatic injuries. Perfect for pediatric trauma programs, this book provides 18 hours of pediatric trauma-specific CME/CE credits, meeting the yearly requirements for trauma-certified professionals.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Children-Wounds and injuries; Electronic books